maʕleš maʕleš: A corpus-based study on the discourse marker maʕleš - Abd El Hafiz, Mukhtar Sayed (AUC Knowledge Fountain, 2019)
This monograph is an attempt to capture the pragmatic functions and the syntactic behavior of the discourse marker maʕleš in Egyptian Colloquial Arabic. It also aims to highlight any potential correlations between the syntactic behavior of maʕleš and its pragmatic functions. Additionally, the collocational behavior of maʕleš within its different pragmatic functions is investigated. The data of this study is a purposeful sample drawn from a corpus of an Egyptian series. Utilizing a corpus-based, qualitative method, the data is analyzed by using WordSmith Tools, a functional corpus software that has the capacity for the search for a word or a set of words at the same time, in addition to the search for the collocations of a particular word. The results of the study are interpreted within the framework of Politeness Theory, as well as Speech Act Theory, based on the notion of the illocutionary force that utterances bring into conversation. The findings of the study show that maʕleš performs as a politeness marker, flagging and/or attenuating a variety of performative acts. Moreover, the findings demonstrate that there is a significant correlation between the illocutions marked by maʕleš and both its syntactic and collocational behaviors.